2007
DOI: 10.1038/nsmb1290
|View full text |Cite
|
Sign up to set email alerts
|

Release of autoinhibition of ASEF by APC leads to CDC42 activation and tumor suppression

Abstract: Autoinhibition of the Rho guanine nucleotide exchange factor ASEF is relieved by interaction with the APC tumor suppressor. Here we show that binding of the armadillo repeats of APC to a 'core APC-binding' (CAB) motif within ASEF, or truncation of the SH3 domain of ASEF, relieves autoinhibition, allowing the specific activation of CDC42. Structural determination of autoinhibited ASEF reveals that the SH3 domain forms an extensive interface with the catalytic DH and PH domains to obstruct binding and activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 43 publications
3
116
0
Order By: Relevance
“…GEF activity of several RhoGEFs of the Dbl type is regulated by the intramolecular autoinhibition. For example, Vav, Dbl, Asef, Tim, and PDZRhoGEF are negatively regulated by their own N-terminal regions (21)(22)(23)(24)(25)(26). Our results demonstrated that the region containing amino acids 212-332 of ARHGEF10 is a negatively regulatory region for its GEF activity.…”
Section: Discussionmentioning
confidence: 99%
“…GEF activity of several RhoGEFs of the Dbl type is regulated by the intramolecular autoinhibition. For example, Vav, Dbl, Asef, Tim, and PDZRhoGEF are negatively regulated by their own N-terminal regions (21)(22)(23)(24)(25)(26). Our results demonstrated that the region containing amino acids 212-332 of ARHGEF10 is a negatively regulatory region for its GEF activity.…”
Section: Discussionmentioning
confidence: 99%
“…APC enhances their GEF activity and thereby regulates cell morphology, adhesion, and migration. In the absence of APC, the activity of Asef is inhibited by the intramolecular interaction between its Dbl homology (DH) and Src homology 3 (SH3) domains (17,18). However, a mutant form of Asef lacking the NH 2 -terminal region exhibits strong GEF activity even in the absence of APC.…”
Section: From the Laboratory Of Molecular And Genetic Information Inmentioning
confidence: 99%
“…The crystal structures of Asef by itself show that its SH3 domain interacts with its DH and PH domains, obstructs the binding of Cdc42 to the DH domain, and autoinhibits its GEF activity [22,24]. On binding to APC, the autoinhibition of Asef is released and the GEF activity of Asef is stimulated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the dissociation constant (K d ) between WT APC-PreARM-ARM and WT Asef-ABR-SH3 proteins was measured to be 17.8 nM by the ITC assay ( Figure 5A, Table 2 Asef-Ala186 and Asef-Asn184, respectively, which are in the center of the core APC-binding motif of Asef-ABR [22]. APC-Asn507 also makes van der Waals contacts with Asef-Leu185 ( Figure 4A).…”
Section: Binding Assays Of the Interaction Between Apc And Asef Usingmentioning
confidence: 99%
See 1 more Smart Citation